2016
DOI: 10.18383/j.tom.2016.00247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MR Imaging Contrast Thresholds on Prediction of Neoadjuvant Chemotherapy Response in Breast Cancer Subtypes: A Subgroup Analysis of the ACRIN 6657/I-SPY 1 TRIAL

Abstract: Functional tumor volume (FTV) measurements by dynamic contrast-enhanced magnetic resonance imaging can predict treatment outcomes for women receiving neoadjuvant chemotherapy for breast cancer. Here, we explore whether the contrast thresholds used to define FTV could be adjusted by breast cancer subtype to improve predictive performance. Absolute FTV and percent change in FTV (ΔFTV) at sequential time-points during treatment were calculated and investigated as predictors of pathologic complete response at surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 37 publications
0
27
0
2
Order By: Relevance
“…Furthermore, quantitative assessments of contrast enhancement intensity at the tumor bed, called lesion-to-background parenchymal signal enhancement ratio (SER), has been shown to improve differentiation between pCR and minimal residual cancer [25]. Other possibilities are the inclusion of tumor regression shrinkage patterns (concentric, nodular or mixed) [26], introduction of subtype-specific contrast enhancement thresholds [27] or integrated fluorodeoxyglucose positron emission tomography (FDG PET)/MRI for early response prediction [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quantitative assessments of contrast enhancement intensity at the tumor bed, called lesion-to-background parenchymal signal enhancement ratio (SER), has been shown to improve differentiation between pCR and minimal residual cancer [25]. Other possibilities are the inclusion of tumor regression shrinkage patterns (concentric, nodular or mixed) [26], introduction of subtype-specific contrast enhancement thresholds [27] or integrated fluorodeoxyglucose positron emission tomography (FDG PET)/MRI for early response prediction [28].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging alone [ 24 26 ] or targeted biopsy techniques [ 27 , 28 ] may be effective tools in determining pCR after NACT. Imaging modalities that show promise in the assessment of chemotherapy response include ultrasound of both breast and axilla [ 24 ], dynamic contrast-enhanced magnetic resonance imaging (MRI) [ 29 ], MRI texture analysis [ 25 ], and trimodal imaging (ultrasound, mammography, and MRI) [ 30 , 31 ]. Shear-wave elastography of tumor stiffness before the start of chemotherapy has been associated with tumor response [ 26 ], and 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) has also been studied [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, we found that functional tumor volume defined by PE threshold set at 70% has the strongest prediction of RFS 17 , 35 and was used to define the tumor region and subsequent segmentation of the stoma in this study. However, this threshold may be unique to each breast cancer subtype and is a subject of our ongoing research 36 , 37 …”
Section: Discussionmentioning
confidence: 99%